Interfacial Assembly of Nanowire Arrays toward Carbonaceous Mesoporous Nanorods and Superstructures. Issue 2 (5th November 2021) - Xie, Lei; Liu, Jinrong; Bao, Xiaobing; Chen, Jiadong; Zheng, Xiaozhong; He, Yanjun; Zhang, Wei; Zeng, Jie; Wang, Yong; Kong, Biao
Abstract: Synthesis of anisotropic carbonaceous nano‐ and micro‐materials with well‐ordered mesoporous structures has attracted increasing attention for a broad scope of applications. Although hard‐templating method has been widely employed, overcoming the viscous forces to prepare anisotropic mesoporous materials is particularly challenging via the universal soft‐templating method, especially from sustainable biomass as a carbon resource. Herein, the synthesis of biomass‐derived nanowire‐arrays based mesoporous nanorods and teeth‐like superstructures is reported, through a simple and straightforward polyelectrolyte assisted soft‐templating hydrothermal carbonization (HTC) approach. A surface energy induced interfacial assembly mechanism with the synergetic interactions between micelles, nanowire, nanorods, and polyelectrolyte is proposed. The polyelectrolyte acts not only as a stabilizer to decrease the surface energy of cylindrical micelles, nanowires and nanorods, but also as a structure‐directing agent to regulate the oriented attachment and anisotropic assembly of micelles, nanowires, and nanorods. After a calcination treatment, the carbon nanorod and teeth‐like superstructure are successfully coupled with Ru to directly produce supported catalysts for the hydrogen evolution reaction, exhibiting much better performance than the isotropic nanospheres based catalyst. This HTC approach will open up new avenues for the synthesis of anisotropic materials with various morphologies and dimensions, expanding the palette of materials selection for many applications. Abstract : Biomass‐derived anisotropic nanowire‐arrays based mesoporous nanorods and teeth‐like superstructures are successfully prepared, through a simple and straightforward polyelectrolyte assisted soft‐templating HTC approach. A surface energy regulated anisotropic interfacial assembly mechanism induced by the synergetic interactions between micelles, nanorods, and PSSMA is then proposed, in which PSSMA acts as not only stabilizer but also structure‐directing agent.